Mechanical Properties and Dielectric Constant of Coconut Coir-Filled Propylene - Lai, Chin Yung (2004)
Natural fiber filler (coconut coir) has an outstanding potential as reinforcement in thermoplastics. The objective of this study is to evaluate the optimum parameters of producing fiber filler composites using coconut coir filler. Experiments were carried out to investigate the effects of three independent variables, namely fiber content, fiber size and different chemical treatment on the mechanical and physical properties of the fiber plastic composites fabricated from coconut coir fiber filler. This study deals with the preparation of coconut coir composites using compression technique in which good interfacial adhesion is generated through blendings of fibers filler modification and matrix.